Analisis Likuiditas Dan Aktivitas Terhadap Profitabilitas Pada Perusahaan Telekomunikasi Yang Terdaftar Di IDX Periode 2021-2023 - Alya Putri Khairunnisa; Diah Yudhawati; Muhammad Nur Rizqi (Jurnal Ekonomi dan Bisnis Digital, 2024)
Companies must be aware of the size of capital needed to carry out their business activities. The ratio known as return on assets or ROA shows how much a company assesses the effectiveness and efficiency of its use of capital in generating profits. All business operations will benefit from a higher ROA value. The purpose of this research is to detect how Return on Assets (ROA) influences and impacts cash turnover, receivables turnover, asset turnover and current ratio in several telecommunications companies recorded on the Indonesia Stock Exchange (IDX) between 2021-2023. Research reveals information using quantitative methodology. Purposive sampling is the sampling process in this test that is applied by researchers. There were 5 companies selected to be used as selected samples for the telecommunications sub-sector recorded on the Indonesia Stock Exchange (IDX) from 2021-2023. The data analysis technique tested was multiple linear regression analysis. This test gives the results that receivables turnover and asset turnover have a significant positive influence on Return on assets (ROA) while cash turnover and current ratio do not have a significant influence on Return on assets (ROA).